2015
DOI: 10.1371/journal.pone.0116929
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of CLK Protein Kinases Suppress Cell Growth and Induce Apoptosis by Modulating Pre-mRNA Splicing

Abstract: Accumulating evidence has demonstrated the importance of alternative splicing in various physiological processes, including the development of different diseases. CDC-like kinases (CLKs) and serine-arginine protein kinases (SRPKs) are components of the splicing machinery that are crucial for exon selection. The discovery of small molecule inhibitors against these kinases is of significant value, not only to delineate the molecular mechanisms of splicing, but also to identify potential therapeutic opportunities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 39 publications
7
111
0
1
Order By: Relevance
“…17 These results, taken together with the recent observations of pronounced modulation of splicing (through inhibition of the CLK mediated phosphorylation of SR proteins 17 ) by compounds such as Araki compound-2 (see Figure 1), 18 strongly suggested that CLK inhibition was responsible for the alternative splicing effects seen with compounds 1 and 2 ; though splicing modulation has not been recognized as an activity of 1 or 2 , to our knowledge. In order to explore the CLKs as possible targets, and to better understand the structure-activity relationships (SAR), additional new structurally related analogs along with the associated CLK biochemical inhibition data were clearly needed so decided to evaluate the most potent of these compounds (compound 1 ) for CLK activity.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…17 These results, taken together with the recent observations of pronounced modulation of splicing (through inhibition of the CLK mediated phosphorylation of SR proteins 17 ) by compounds such as Araki compound-2 (see Figure 1), 18 strongly suggested that CLK inhibition was responsible for the alternative splicing effects seen with compounds 1 and 2 ; though splicing modulation has not been recognized as an activity of 1 or 2 , to our knowledge. In order to explore the CLKs as possible targets, and to better understand the structure-activity relationships (SAR), additional new structurally related analogs along with the associated CLK biochemical inhibition data were clearly needed so decided to evaluate the most potent of these compounds (compound 1 ) for CLK activity.…”
Section: Resultsmentioning
confidence: 53%
“…However, since it known that CLK inhibition can lead to modulation of pre-mRNA splicing, 18 and since we observed that the weakly cell-active, but selective, CLK inhibitor KH-CB19 shows activity in the MDM2-Luc reporter assay, we decided to explore the activity of 1 (and our active analogs) in regard to their biochemical inhibition of CLK 1-4 (see Table 2). The results summarized in Table 2 clearly show that CGP-74514A ( 1 ), which has been considered a selective CDK inhibitor 46 actually also shows significant inhibition of CLK 1, 2, and 4 and so can be considered a dual CLK/CDK inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), by chemical modifications of the structure of previously identified tool compounds 22 from an extensive high throughput chemical library screen against CLK2 protein (Supplementary Tables 1, 2). The structure–activity relationship (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SR proteins have conserved arginine- and serine-rich domains, which are subject to phosphorylation by multiple kinases, including the SR protein kinases and the CDC2-like kinases. Although the role of phosphorylation of these domains remains to be clarified, modulation of SR protein phosphorylation clearly impacts splicing (68, 69). Characterization of the effects of these new classes of compounds on splicing and potential effects on spliceosomal-mutant malignancies may represent novel therapeutic approaches for conquering malignancies with aberrant spliceosomal catalysis.…”
Section: Open Questionsmentioning
confidence: 99%